Independent calculation of dose distributions for helical tomotherapy using a conventional treatment planning system. Issue 8 (30th November 2016) - Klüter, Sebastian; Schubert, Kai; Lissner, Steffen; Sterzing, Florian; Oetzel, Dieter; Debus, Jürgen; Schlegel, Wolfgang; Oelfke, Uwe; Nill, Simeon
Abstract : Purpose: The dosimetric verification of treatment plans in helical tomotherapy usually is carried out via verification measurements. In this study, a method for independent dose calculation of tomotherapy treatment plans is presented, that uses a conventional treatment planning system with a pencil kernel dose calculation algorithm for generation of verification dose distributions based on patient CT data. Methods: A pencil beam algorithm that directly uses measured beam data was configured for dose calculation for a tomotherapy machine. Tomotherapy treatment plans were converted into a format readable by an in‐house treatment planning system by assigning each projection to one static treatment field and shifting the calculation isocenter for each field in order to account for the couch movement. The modulation of the fluence for each projection is read out of the delivery sinogram, and with the kernel‐based dose calculation, this information can directly be used for dose calculation without the need for decomposition of the sinogram. The sinogram values are only corrected for leaf output and leaf latency. Using the converted treatment plans, dose was recalculated with the independent treatment planning system. Multiple treatment plans ranging from simple static fields to real patient treatment plans were calculated using the new approach and either compared to actual measurements or the 3D dose distribution calculated by the tomotherapy treatment planning system. In addition, dose–volume histograms were calculated for the patient plans. Results: Except for minor deviations at the maximum field size, the pencil beam dose calculation for static beams agreed with measurements in a water tank within 2%/2 mm. A mean deviation to point dose measurements in the cheese phantom of 0.89% ± 0.81% was found for unmodulated helical plans. A mean voxel‐based deviation of −0.67% ± 1.11% for all voxels in the respective high dose region (dose values >80%), and a mean local voxel‐based deviation of −2.41% ± 0.75% for all voxels with dose values >20% were found for 11 modulated plans in the cheese phantom. Averaged over nine patient plans, the deviations amounted to −0.14% ± 1.97% (voxels >80%) and −0.95% ± 2.27% (>20%, local deviations). For a lung case, mean voxel‐based deviations of more than 4% were found, while for all other patient plans, all mean voxel‐based deviations were within ±2.4%. Conclusions: The presented method is suitable for independent dose calculation for helical tomotherapy within the known limitations of the pencil beam algorithm. It can serve as verification of the primary dose calculation and thereby reduce the need for time‐consuming measurements. By using the patient anatomy and generating full 3D dose data, and combined with measurements of additional machine parameters, it can substantially contribute to overall patient safety.